2022
DOI: 10.3389/fnut.2022.1001031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary resveratrol on placental function and reproductive performance of late pregnancy sows

Abstract: Placental function is vital to the fetal growth of sows, and resveratrol (RES) can protect cells against oxidative stress, which is one of the major factors impairing placental function. This study aimed to investigate the effect of dietary resveratrol (RES) on placental function and reproductive performance during late pregnancy in a sow model from the aspects of oxidative stress, insulin resistance, and gut microbiota. A total of 26 hybrid pregnant sows (Landrace × Yorkshire) with similar parity were randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…We found that adding SeY and GML to the diet increased the beneficial bacteria (Christensenellaceae_R-7_group, Clostridium_sensus_stricto_1, Bacteroidota) abundance and decreacsed the F/B ratio. Christensenellaceae_R-7_group is associated with enhancing intestinal barrier integrity and reducing oxidative stress in the body [33,34]. Clostrid-ium_sensus_stricto_1 has been reported to promote the health of the intestinal barrier by producing short-chain fatty acids (SCFAs), maintain the integrity of the intestinal barrier, and help reduce the entry and penetration of LPS [35,36].…”
Section: Selenium and Gml Reshape Sow Gut Microbiota Composition To M...mentioning
confidence: 99%
“…We found that adding SeY and GML to the diet increased the beneficial bacteria (Christensenellaceae_R-7_group, Clostridium_sensus_stricto_1, Bacteroidota) abundance and decreacsed the F/B ratio. Christensenellaceae_R-7_group is associated with enhancing intestinal barrier integrity and reducing oxidative stress in the body [33,34]. Clostrid-ium_sensus_stricto_1 has been reported to promote the health of the intestinal barrier by producing short-chain fatty acids (SCFAs), maintain the integrity of the intestinal barrier, and help reduce the entry and penetration of LPS [35,36].…”
Section: Selenium and Gml Reshape Sow Gut Microbiota Composition To M...mentioning
confidence: 99%
“…13 Furthermore, studies have shown that resveratrol may reduce fat deposition and improve energy metabolism by upregulating AMPK expression. [14][15][16][17] Moreover, resveratrol has the potential to alleviate maternal oxidative stress in late pregnancy in sows, 18 promote fetal growth in murine models with reduced blood supply to the uterus, 19 and alleviate gestational diabetes mellitus (GDM) in model mice. 20 These findings suggest that resveratrol may alleviate adverse pregnancy outcomes by regulating maternal metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Several strategies have been used to address insulin resistance in late-pregnancy and lactation phases in sows. For instance, supplementing diets with soluble fiber or resveratrol has shown promise in alleviating periparturient insulin resistance by modulating the gut microbiota [ 9 , 10 ]. However, the conclusions from these studies are inconsistent.…”
Section: Introductionmentioning
confidence: 99%